The effects of specific preconditioning activities on acute sprint performance - Guggenheimer, J. D.; Dickin, D. C.; Reyes, G. F.; Dolny, D. G. (The Journal of Strength and Conditioning Research, 2009)
Previous research suggests that specific preconditioning activities such as whole-body vibration (WBV) and resistance training may play an important role in ensuing dynamic activities. The purpose of this study was to examine the effects of 2 preconditioning activities, WBV and power cleans (PC), on acute sprint performance. Two studies were conducted in which 14 (WBV) and 9 (PC) male track and field athletes were subjects. The WBV treatment consisted of 4 bouts of 5 seconds of high-knee running on a vibrating platform at 0, 30, 40, or 50 Hz. The PC treatment consisted of 3 PC reps at 90% 1RM. In both cases, acute sprint performance was the dependent variable of interest. For WBV, split times were recorded at 10, 20, and 40 m. Reaction times (RXN) as well as 5-, 10-, and 40-m split times were recorded for the PC study. Results indicated no significant differences between treatment and nontreatment groups for both studies. However, significant correlations were present between RXN and 5-m splits (r = 0.65) and RXN and 10-m splits (r = 0.63), although they decreased as a function of sprint distance to r = 0.43 at 40 m. These results suggest little efficacy for the use of WBV and PC as a means of augmenting acute sprint performance. However, a trend within the 30-Hz protocol may suggest that WBV as part of a warm-up for sprinting activities greater than 40 m (i.e., 100 m) could potentially result in a decreased sprint time of nearly 1/10th of a second, which is worth future consideration.